Working for Justice : The L.A. Model of Organizing and Advocacy - Narro, Victor, 1963-; Bloom, Joshua; Milkman, Ruth, 1954- (Book collections on Project MUSE., 2010)
The organised labour movement in Los Angeles has weathered the effects of deindustrialization and deregulation better than unions in other parts of the U.S., and this has helped to anchor the city's wider low-wage worker movement.